Kemitraan Pusat Pelayanan Terpadu Pemberdayaan Perempuan Dan Anak (P2TP2A) Dengan Pemerintah Desa Dalam Upaya Pemberdayaan Serta Perlindungan Anak Di Desa Benan Kabupaten Lingga - Ema Sapitri; Edy Akhyary; Agus Hendrayady (Universitas Sains dan Teknologi Komputer, 2023)
P2TP2A (Center for Integrated Services for Women and Children Empowerment) is an institution established by the government to provide integrated services for women and children who are victims of violence. One of P2TP2A's tasks is to provide protection and empowerment of children who are victims of violence. This study was conducted to analyze the pattern of partnership relations between the Integrated Service Center for Women and Children Empowerment (P2TP2A) and Village Government in efforts to empower and protect children in Benan Village and the obstacles faced in these partnerships and solutions provided using the partnership model theory according to Notoatmoadjo which consists of two partnership models, namely, Model I and Model II. This research also has programs and obstacles born from these programs. The method used in this study is descriptive research in a qualitative approach. This research was conducted at the Integrated Service Center for Women and Children Empowerment (P2TP2A) and the Benan Village Government. Based on research that has been conducted that the partnership between the Integrated Service Center for Women and Children Empowerment (P2TP2A) and the Village Government in efforts to empower and protect children in Benan Village is included in the partnership model I. This partnership program in P2TP2A has led to efforts to empower and protect children. However, in implementing the program, of course, there are obstacles that hinder. The constraint is the budget. To achieve the success of a partnership, the Integrated Service Center for Women and Children Empowerment (P2TP2A) and the Benan Village Government work together to make a report to the district government to increase the activity budget so that they can carry out socializing activities in all villages around Benan Village, Katang Bidare District.